Exploration of Degradation Mechanism of Chlorogenic Acids in Stevia Based on UPLC-QTOF MS/MS - Juan-juan WU; Zi-xuan WANG; Yun-he LIAN; Li-juan HOU; Zhi-ping NIU; Wen-chang WANG; Di WU (Zhipu Xuebao)
Chlorogenic acids (caffeoylquinic acids, CQAs), as key bioactive components in numerous traditional herbal medicines, are highly acclaimed for their various biological activities and therapeutic benefits. Nonetheless, their stability and therapeutic utility are challenged by the propensity to degrade under various environmental stimuli, including exposure to light, temperature fluctuations, and changes in pH levels. This inherent instability may lead to substantial losses, compromising the potency and consistency of herbal formulations and their derivative products. Therefore, high-performance liquid chromatography (HPLC) was employed to assess the content variation of seven chlorogenic acid derivatives, namely 3-caffeoylquinic acid (3-CQA), 4-caffeoylquinic acid (4-CQA), 5-caffeoylquinic acid (5-CQA), caffeic acid, 3,4-di-caffeoylquinic acid (3,4-diCQA), 3,5-di-caffeoylquinic acid (3,5-diCQA) and 4,5-di-caffeoylquinic acid (4,5-diCQA) in the stevia chlorogenic acid samples subjected to environmental stimuli. Furthermore, ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-QTOF MS/MS) was utilized to identify the degradation products of stevia chlorogenic acids under various induced conditions. Based on these degradation products, potential degradation pathways of stevia chlorogenic acids were inferred. The results indicated that stevia chlorogenic acids undergo degradation under induced conditions such as solvent exposure, light irradiation, high temperature, and varying pH levels, leading to a general decrease in total content of CQAs. The analysis of degradation products showed that both CQAs and diCQAs are prone to alkylate when stored in organic solvents such as alcohols and esters, resulting in alkylated chlorogenic acids. Under light exposure, they tend to degrade into caffeic acids. In high temperature environment, both dehydration and alkylation occur, producing dehydrated chlorogenic acids and further alkylated derivatives. In acidic or alkaline conditions, hydrolysis and structural transformations are common degradation pathways observed. In summary, dehydration, degradation, hydrolysis, and isomerization are four potential pathways of loss for stevia-derived chlorogenic acids subjected to environmental fluctuations. This study not only enhances the understanding of the stability mechanisms of chlorogenic acids, but also provides a scientific basis and practical guidance for formulating effective preservation strategy. This strategy is crucial for ensuring quality control of chlorogenic acid-containing products across various industries, including pharmaceuticals, health supplements, and cosmetics. By mitigating these degradation pathways, manufacturers can more effectively preserve the potency and efficacy of these compounds, thereby contributing to the overall quality and reliability of their products.